Disseminated cutaneous sporotrichosis: unusual presentation in an alcoholic patient - Mariana de Freitas Valente; Amanda Bertazzoli Diogo; Vitoria Flores Culau Merlo; José Roberto Pereira Pegas (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
ABSTRACT Sporotrichosis is an implantation mycosis highly prevalent in Brazil, associated with soil activities and contact with infected animals. It has numerous clinical manifestations and its disseminated cutaneous form is uncommon, found in approximately 4% of cases and usually related to immunosuppressive conditions. We report an alcoholic 56-year-old male patient with no other comorbidities, presenting with multiple cutaneous nodules and ulcers. The patient was diagnosed with disseminated cutaneous sporotrichosis based on the isolation and identification of Sporothrix spp. The patient was initially treated with amphotericin B with satisfactory results and then with itraconazole.